The Impact of Different Level of Education Towards Acceptance of Islamic House Financing - Abd Aziz, Noriza; Abu Bakar, Azizi; Abd Aziz, Ibrahim; Yusuff, Noraini; Ahmad Musadik, Siti Hajar Salwa (Academic & Scientific Publisher, 2021)
Home ownerships are a necessity to all Malaysians. A natural sequence in life, after completing their studies and getting their „dream jobs?. Often times, following their nuptials, so that they could focus on raising a family in a proper environment, in their own homes. There are many housing developers offering various types of residential properties to cater to the demands from consumers with diverse economic backgrounds. In order to finance their purchases, these consumers would turn to the banks to choose the suitable house financing products. Competitions among financial institutions seeking to win „good? customers provide an opportunity for the consumers to survey for the best deals in house financing. These competitions pose a challenge to the banks to maintain their profit levels. The introduction of Shariah-compliant Islamic house financing products and services is embraced by many Muslim customers as obligatory and as a duty. Now, many Muslim and non-Muslim consumers are beginning to understand and trust Islamic banks and Islamic house financing products and services. Islamic banks perform the same essential functions as the conventional banks, except that Islamic banks are being guided by Shariah principles in their activities as well as products and services. Past studies found that the reasons for selecting Islamic house financing products from Islamic banks are not solely based on religion, but a combination of religious, demographic, age, gender, attitudes, perception, awareness, understanding and other factors such as promotion and service. This paper had focused on the customers? level of education, and the extent of the impact their education have on their acceptance of Islamic house financing. The finding shall enable banks to better understand and recognize this one aspect of the criteria in choosing Islamic house financing, and how these categories of customers should be pursued. This study revealed that the level of education of the customers was a significant factor influencing their decisions to select Islamic banking products and services. Consumers with high level of education tend to have greater knowledge of Islamic banking and the mechanism of Islamic banking products. At the same time, they also tend to be technologically adept and information savvy, and have the competency to grasp the working mechanism of Islamic house financing, and also have the level of knowledge, understanding and awareness to differentiate between Islamic banking products and conventional banking products